ANALISIS KARAKTERISTIK KECELAKAAN LALU LINTAS JALAN SITINJAU LAUIK KOTA PADANG - andre, bhareta; Yulfa, Arie (JURNAL BUANA, 2025)
Highways are the main means of transportation activities as a connecting access between locations. Traffic and road transport have a strategic squeeze in supporting economic development in an effort for the general welfare. This study aims to determine the cause of the accident in Panorama 1 and Panorama 2 Sitinjau Lauik Padang City. This research is included in the type of descriptive research with methods using quantitative and qualitative approaches. The results showed that accidents on Panorama 1 occurred mostly at 12:01-18:00 on weekdays with a total of 7 incidents and Panorama 2 at 18:01-00:00 on weekdays with a total of 8 incidents. In addition, the speed and facilities of the road also trigger accidents.